2023
DOI: 10.1007/s12519-023-00764-0
|View full text |Cite
|
Sign up to set email alerts
|

Superior antibody and membrane protein-specific T-cell responses to CoronaVac by intradermal versus intramuscular routes in adolescents

Jaime S. Rosa Duque,
Samuel M. S. Cheng,
Carolyn A. Cohen
et al.

Abstract: Background Optimising the immunogenicity of COVID-19 vaccines to improve their protection against disease is necessary. Fractional dosing by intradermal (ID) administration has been shown to be equally immunogenic as intramuscular (IM) administration for several vaccines, but the immunogenicity of ID inactivated whole severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the full dose is unknown. This study (NCT04800133) investigated the superiority of antibody and T-cell responses of f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…It thus seems that the development of immunological memory does not impact the neutralizing antibody capacity as much as the IgG titers. A two-dose intramuscular mRNA vaccination was performed, however, a recent pediatric study showed that an alternative administration route via intradermal SARS-CoV-2 vaccination could be beneficial compared to intramuscular vaccination with superior antibody responses [ 40 ]. Nevertheless, this proposed method requires further research [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It thus seems that the development of immunological memory does not impact the neutralizing antibody capacity as much as the IgG titers. A two-dose intramuscular mRNA vaccination was performed, however, a recent pediatric study showed that an alternative administration route via intradermal SARS-CoV-2 vaccination could be beneficial compared to intramuscular vaccination with superior antibody responses [ 40 ]. Nevertheless, this proposed method requires further research [ 41 ].…”
Section: Discussionmentioning
confidence: 99%